Keterlibatan, Keberhargaan, dan Kompetensi Sosial sebagai Prediktor Kompetisi pada Remaja - Santoso, Singgih Wibowo (Jurnal Psikologi, 2011)
Competition is a common phenomenon among adolescents, that shows the drives to express the ability, to compare self with others, and to strive to be the best. This study wasaimed to assess whether the engagement, sense of worth, and social competence can be the predictors of the emergence of competition in adolescents. Subjects were amounted to 232students, including the students from favorite and non-favorite junior and high school in the city of Yogyakarta and Gunungkidul. The instrument used were the engagement’ scale, senseof worth’ scale, social competence’ scale, and competition’ scale. The data then were analized using regression approach and also t-test for additional analysis. The results showed that therewas the influence of engagement, sense of worth, and social competence to the competition (F=65.274, p<0.01). Taken together anyway, engagement, sense of worth, and socialcompetence in adolescents can predict competition for 46.3% (R2=0.463). Based on t-test as an additional analysis of the obtained results that there is a difference in competition betweenfavorite and non-favorite schools. Competition in non-favorite schools is higher (t=–2.752, p<0.01) than favorite ones. In addition, there is a difference of social competence between theschool in Gunungkidul and Yogyakarta. Social competence of students in Gunungkidul is higher than students in Yogyakarta (t=–2.083, p<0.05). Another result shows that competitionamong the students in favorite schools is lower than in non-favorites ones (t=–2.752, p<0.01). Especially for high school students, the result showed that high school students' socialcompetence in Gunungkidul is higher than in Yogyakarta (t=–3.966, p<0.05) and social competence of favorite high school students are lower than non-favorite high school students.